KOORDINASI APARAT PENGAWASAN INTERN PEMERINTAH (APIP) DAN PENYIDIK DALAM PENANGANAN TINDAK PIDANA KORUPSI DI KABUPATEN BANYUMAS - Nunik Sri Wahyuni (MIH Unsoed, 2017)
This research aimed to find out the form and coordination effectiveness between the Government Intern Controlling Apparatus with the Investigator in handling the criminal act of corruption in the Regency of Banyumas This research used the sociology juridical approach. Data in this research was obtained by interview with the Public Attorney Investigator of Banyumas. The Tipikor Unit Investigator Reskrim Polres Banyumas and Inspektorat Banyumas and collecting many of the certainty ordinance regulation, documentation, literature and accessing internet. Based on the result of research and discussion could be taken the conclusion of. Coordination between APIP and Investigator did not have the clearness in technique and criteria act of State Civil Apparatus which one was categorized in the scope of criminal act that became the authority of Investigator or in the scope of administration that became the authority of APIP with the Investigator in handling the criminal act of corruption was not being effective because of ego sectoral between APIP and Investigator and the necessity of disposition of regebts so that APIP can not work objectively and take a very long time. Keywords: APIP, Coordination, Investigator